The Effects of Model Project-Based Learning Approach on STEM (Science, Technology, Engineering, Mathematic) on Natural Science Learning to Junior High School Student’s Critical Thinking Skills And Cooperative Skills at SMP N 1 Berbah - Riyani Septi Indriyana; Susilowati Susilowati (Journal of Science Education Research, 2020)
This research aimed to (1) analyzes the effect of model project-based learning approach STEM (science, technology, engineering, mathematics) on natural science learning to junior high school student’s critical thinking skills and cooperative skills, and (2) analyze how the effect of model project-based learning on STEM (science, technology, engineering, mathematics) on natural science learning to junior high school student’s critical thinking skills and cooperative skills. This research was quasi-experimental with a non-equivalent control group design. The population was eighth-grade students of SMP Negeri 1 Berbah. Sampling selection technique used cluster random sampling techniques and obtained class VIII B as an experimental class and class VIII C as a control class. Learning in the experimental class project-based learning model was STEM-oriented, and the control class used a scientific approach. The data were pretest and posttest critical thinking, observation sheets of cooperative. The analysis used the normality test, homogeneity test, MANOVA test, and effect size. The results showed that: (1) there was an effect of project-based learning model on STEM approach on critical thinking skills and cooperative skills of students of SMP Negeri 1 Berbah, (2) the effect of science learning project-based learning model on STEM approach on critical thinking and collaborative skill was on medium category.